2017
DOI: 10.1002/hed.24910
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of pAKT(Ser473) expression in progression of HPV‐positive oropharyngeal squamous cell carcinoma

Abstract: Activation of phosphoinositide 3-kinase (PI3K)/pAKT(Ser473) frequently occurs in advanced HPV-positive oropharyngeal SCC and elevated pAKT(Ser473) levels represent a feature during progression of oropharyngeal SCC, indicating a critical role of the mammalian target of rapamycin (mTOR) complex. Further studies are required to evaluate specific drugs targeting PI3K/AKT/mTOR in consideration of PIK3CA alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…PI3k/AKT pathway is one of the major signaling cascades overactivated in various tumor entities including OPSCC [29]. To gain insight into the correlation of PI3k/AKT and MEK1-ERK1/2 pathway in OPSCC, pERK1/2 staining patterns were compared with data for pAKT (Ser473) phosphorylation, which were assessed previously [25]. IRS data for both pERK1/2 and pAKT (Ser473) were available for 109 cases of our OPSCC cohort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3k/AKT pathway is one of the major signaling cascades overactivated in various tumor entities including OPSCC [29]. To gain insight into the correlation of PI3k/AKT and MEK1-ERK1/2 pathway in OPSCC, pERK1/2 staining patterns were compared with data for pAKT (Ser473) phosphorylation, which were assessed previously [25]. IRS data for both pERK1/2 and pAKT (Ser473) were available for 109 cases of our OPSCC cohort.…”
Section: Resultsmentioning
confidence: 99%
“…HPV-positive oropharyngeal SCC showed activating mutations of PIK3CA in 56% [24]. In a recent study, we found pAKT (Ser473) expression serves as an independent prognostic marker for progression-free survival in OPSCC [25]. So far, only inhibitors of the epidermal growth factor receptor (EGFR) upstream of MAPK/ERK signaling have gained approval for HNSCC treatment [26].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, pAKT (Ser473) expression increased in primary tumors to progressive nodal disease (21.1%; P < 0.011; ref. 25).…”
Section: Akt As a Target In Cancer Therapymentioning
confidence: 99%
“…[25][26][27][28][29] The score for each individual ranged from 1 to 16 and was calculated by multiplication of score A and B. Secondary antibody detection was performed using the DAKO Real Kit (DAKO, Hamburg, Germany) according to the manufacturer's protocol.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The established scoring system was applied as previously described. [25][26][27][28][29] The score for each individual ranged from 1 to 16 and was calculated by multiplication of score A and B. Scores from 0 to 8 were combined in the CTTN low group.…”
Section: Immunohistochemistrymentioning
confidence: 99%